Dialects of the azerbaijan language and common language units in “kitab al-idrak li-lisan alatrak" by asiraddin abu hayyan al-andalusi - QALİBƏ (Uluslararası Türk Lehçe Araştırmaları Dergisi)
In the historical study of contemporary Turkic languages and dialects, primary sources include not only spoken language and folklore but also ancient written literary-historical works in Turkish. Additionally, theoretical studies on the Turkish language by foreign researchers from different periods are considered crucial. One of the most valuable historical sources for the historical and dialectological study of Turkic languages is the work “Kitab al-idrak li-lisan alatrak” by the 14th -century Arab scholar Asireddin Abu Hayyan al-Andalusi. The first part of this work, which is composed of two sections, contains a dictionary spanning approximately 135 pages. The second section, comprising 51 pages, is dedicated to the grammatical rules of the Old Kypchak Turkic language. Abu Hayyan’s research on the Old Kypchak Turkic language demonstrates that it played a significant role in the formation of the literary language of Azerbaijan, which belongs to the Oghuz-Seljuk subgroup of the Oghuz branch within the Turkic language family. The work contains very interesting information about the history of Turkic languages, including Azerbaijani Turkic. Through this work, it is possible to trace the history of linguistic creativity in contemporary Azerbaijani and Turkish languages, as well as to explore the historical ethnolinguistic layers of Azerbaijani and Anatolian dialects. Sufficient material is also available to easily trace the historical lexical-semantic and grammatical characteristics of this language, as well as the ancient Azerbaijani-Turkish onomastic system. Considering that 80-90% of the words in Abu Hayyan's dictionary dedicated to the Kipchak language — such as burku-hot, argun – slow, budamag – to prune the branches, bacanaq – sisters’ spouses, birchek – fringe, bardmak – to go, burunduruq – yoke, burğu – drill, birükdirmek – to collect, berkitmək – to sweeten the place, büzmək — to sqeeze, irtəearly, yürəksiz – coward, yığın - pile, yorğa – slow, göyünmək – to hurt, , muştuqi – foggy, kilit – key, kərki – chopping tool, qavut – roasted wheat, çisə - light rainare used both in literary language and dialects of modern Azerbaijani and Turkish languages, we can observe that the Kipchak language, like the Oghuz language, played a significant role in shaping modern Azerbaijani and Turkish.